Implementing Azure Solutions : Deploy and manage Azure containers and build Azure solutions with ease, 2nd Edition /: Deploy and manage Azure containers and build Azure solutions with ease, 2nd Edition. (2018) - Klaffenbach, Florian; Klein, Markus; Hoppe, Sebastian; Michalski, Oliver; Damaschke, Jan-Henrik
No abstract available